Assessing Self-Confidence Levels Among Students Engaged in Dubbing Video Activities - Hasbiyati; Dwi Nur Hadiansyah W; M Hilmy Hidayatullah; Fathol Qorib (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to assess the impact of dubbing video activities on students’ self-confidence levels. Theoretical framework: This study is based on Bandura’s theory, which emphasizes self-confidence as a crucial factor in students’ ability to maximize their performance in the teaching and learning process. However, a low level of self-confidence remains a persistent challenge, particularly in Indonesia, where language anxiety and fear of making mistakes hinder students from expressing themselves. Literature review: This study includes a study of the effectiveness of using dubbing video as the learning media in increasing students’ self-confidence levels using a questionnaire based on three indicators of Lindefield and Lauster’s theory. Methods: Using a pre-experimental one-group pretest-posttest design, the research involved 30 ninth-grade students at a junior high school in Mumbulsari, East Java. Students completed a self-assessment questionnaire using a 5-point Likert scale before and after the treatment. Result: The results show a significant improvement in students’ self-confidence after participating in the dubbing video activities. The mean score increased from 79.93 (pretest) to 90.67 (posttest). The data were normally distributed, linear, and allowed for valid parametric analysis. A paired sample t-test revealed a significant difference with a p-value < 0.001, indicating that the dubbing video activity had a statistically significant positive effect on students’ self-confidence. Implications: Overall, dubbing video activities are effective in enhancing students’ self-confidence. They offer a creative, low-anxiety environment that encourages expression and builds learners’ belief in their ability to use English successfully. Novelty: This study emphasizes and focuses on the vital aspect that students should master before mastering another aspect of learning English. This study also proposes dubbing video as a learning medium to be a new technological approach to increase students' confidence levels.